Cowgirl Grit - Jake Maddox (Stone Arch Books, 2018)
Sydney Todachine is stuck at her grandfather's ranch for the summer, and she's feeling out of place. So when Sydney bonds with a beautiful horse, she decides to ride in secret rather than risk embarrassing herself in front of the experienced cowboys and cowgirls. But as rider and horse practice pole bending, will Sydney find the courage to face her fears and compete in the upcoming rodeo? Each book in Jake Maddox Girl Sports Stories features easy-to-read text, fast-paced action, plus back matter support materials to make it a winning read.
Keywords: Sport Stories -- Sport Stories